Balanced Scorecard sebagai Metode Pengukuran Efektivitas Strategi Competitive Advantage Pt. X dalam Menghadapi Kondisi Vuca - Dian Widhasari; Noviaty Kresna Darmasetiawan (Syntax Corporation, 2023)
The current business conditions are experiencing major challenges with the occurrence of globalization. This is further complicated by the occurrence of VUCA due to the COVID-19 pandemic that occurred in the last 2 years. Business challenges that initially focused only on globalization, now must focus more on determining the right strategy to face business competition while surviving the VUCA conditions due to the COVID-19 pandemic. This research was conducted at PT. X, who managed to survive the VUCA condition due to the COVID-19 pandemic by using the BSC method to measure the effectiveness of the competitive advantage strategy that the company has used